The Difference between the Western European and German Ideas of Nationalism - Ziętek-Wielomska, Magdalena (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
Scientific research leaves no doubt that criminal National Socialism is not an archetype of nationalism or a national doctrine. It is a common view that the nationalist ideology was born in revolutionary France and the United States of America. For political reasons, the truth about the diametrically different nature of Western nationalism – primarily French and Anglocentric – on the one hand, and German on the other, is blurred. In the era of the spread of globalist cosmopolitanism ideology, national ideas are treated as the greatest danger to the progress of humanity.